Studi Kasus: Paraplegia Lumbosacral Akibat Traumatik pada Anak Kucing Lokal - Kusumaning Arumsari Wimbavitrati; I Wayan Batan; I Made Suma Anthara (Universitas Sulawesi Barat, 2020)
A local female cat who was ±3 months old with a body weight of 1.5 kg presented to hind legs with complaints of being unable to stand. The inspection showed that the cat was not able to stand upright especially on its two hind legs. When palpated, the hind legs muscle tension begins to decrease. Based on the postural examination, pelvic limb reflexes, and nociceptive examinations, it was pointed to an abnormal disturbance in both hind legs and additionally, there was no response anal sphincter area. A series of neurological examinations indicated that the cat had a lumbosacral nerve disorder. Hematological examinations suggesting the anemia indicated. X-ray examination showed the fracture of an os. vertebrae lumbar I. The cat was diagnosed with paraplegia due to a trauma, where the muscles of the body are paralyzed and weak. The prognosis for this case was infausta. Medications and therapies provided were neurotropic vitamins, dexamethasone, and Hemobion®, and train cats to stand and walk every day. After being given treatment for ten days, the cat case did not show any changes in the two hind legs.